2018
DOI: 10.1103/physrevb.97.014312
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced transitions in magnetoresistive manganites: A comprehensive view

Abstract: We use femtosecond x-ray diffraction to study the structural response of charge and orbitally ordered Pr 1−x Ca x MnO 3 thin films across a phase transition induced by 800 nm laser pulses. By investigating the dynamics of both superlattice reflections and regular Bragg peaks, we disentangle the different structural contributions and analyze their relevant time-scales. The dynamics of the structural and charge order response are qualitatively different when excited above and below a critical fluence f c . For e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…2b). While a NIR pump can also excite free carriers in the system, the linear fluence dependence below the saturation threshold supports the notion that the pump induced reflectivity change at 1.55 eV must mainly come from the above-the-band-gap electronic excitations [11,14,29,33]. This is supported by the strongly gapped optical mode (Fig.…”
supporting
confidence: 67%
“…2b). While a NIR pump can also excite free carriers in the system, the linear fluence dependence below the saturation threshold supports the notion that the pump induced reflectivity change at 1.55 eV must mainly come from the above-the-band-gap electronic excitations [11,14,29,33]. This is supported by the strongly gapped optical mode (Fig.…”
supporting
confidence: 67%
“…The deviation of the model to the highest-fluence data is likely due to the remaining weakly excited regions of the probed volume due to an uncertainty in the determination of the pump and probe depths, particularly for bulk crystals. In addition, the high fluence data are further affected by an incomplete recovery between successive pump pulses, as was recently observed for 3D PCMO [23]: For fluences higher than required to fully melt the CO/OO order at the surface, the diffraction intensity no longer completely recovers between successive pump pulses due to the first-order character of the CO/OO transition, which results in slow dynamics of domain growth. The highest fluence time trace where this effect is largest was thus not included in the fitting procedure.…”
Section: Ultrafast Dynamics Of the Co/oo Induced Structural Distormentioning
confidence: 81%
“…The ultrafast dynamics of electronic and magnetic phase transitions in manganites have been extensively studied [12][13][14][15][16][17][18][19]. In particular, resolving the structural dynamics in three-dimensional (3D) manganites following the photoinduced melting of the charge and orbital ordered (CO/OO) phase has been addressed in detail [11,[20][21][22][23][24]. It has been shown that a single order parameter that depends only on the electronic excitation is sufficient to describe the photoinduced ultrafast phase transition of the entire system, including charge and structural degrees of freedom [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the scale factors g x , g y and g z are dynamical variables, which describe long-wave length acoustic modes that are responsible for the strain effects in manganites [23,24]. We enforce g x = g y .…”
Section: Strain Dynamicsmentioning
confidence: 99%